Fortresses of the Peloponnese, Ottoman Defences and the Greek Revolution (1821–1828) - Özkan Pantazis, Dilek (Historein, 2023)
During the Greek Revolution, the fortresses of the Peloponnese played a crucial role, serving as key defensive positions, sanctuaries for those seeking refuge from violence and sites for negotiations between the Ottoman forces and Greek revolutionaries. By maintaining control over a handful of fortresses in the Morea, the Ottomans were able to monitor the progress of the uprisings. However, their claim to rule persisted until they were eventually compelled to evacuate by French forces in 1828. This article seeks to address the Ottoman presence in the Peloponnese. It explores the whereabouts of Ottoman forces, their defensive strategies against the Greek revolutionaries and the factors that contributed to their successes or failures in confronting the Greek forces. Additionally, it delves into the impact of the physical characteristics of the fortresses, the geography of the region and the weather conditions during the Greek uprising. Focusing primarily on the fortresses of the Peloponnese, the article draws from Ottoman archival documents to shed light on the Ottoman perspective of the Greek revolts.